A light-driven supramolecular nanowire actuator1. Issue 15 (21st April 2015) - Lee, Junho; Oh, Seungwhan; Pyo, Jaeyeon; Kim, Jong-Man; Je, Jung Ho
<x xml:space="preserve">Abstract</x> Single light-driven molecular nanowire actuator is first developed that employs the azobenzene-containing tris(4-((E)-phenyldiazenyl)phenyl)-benzene-1, 3, 5-tricarboxamide (Azo-1). Single Azo-1 nanowires undergo bending upon irradiation with UV light that is reversed upon visible light irradiation, and the bending behavior follows first-order kinetics associated with azobenzene photoisomerization.